Preparation method and application of multifunctional granular hydrogel based on ammonia-epoxy reaction

Through the combination of amine-epoxy reaction and sodium lignin sulfonate, the microstructure of the hydrogel is regulated to form a granular hydrogel with versatility and antioxidant functions, which solves the problem of insufficient material performance in the prior art. It has achieved application in the fields of tissue engineering and wound healing.

CN119192815APending Publication Date: 2024-12-27OUJIANG LAB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411362949.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The prior art is difficult to prepare mass-produced granular hydrogel materials with specific microstructure and versatility, especially in the fields of tissue engineering, drug controlled release and wound healing.

Method used

Through the amine-epoxy reaction combined with the introduction of sodium lignin sulfonate, the internal micromorphology of the hydrogel is regulated to form a granular hydrogel loaded with hydrophobic drugs and antioxidant functions, using amino groups to promote cell adhesion, and Interconnected hydrogel microparticles are formed through non-covalent action and ammonia-epoxy click chemical reaction.

Benefits of technology

It has realized the preparation of granular hydrogels with versatility and control of micromorphology and mechanical strength, which can load hydrophobic drugs, reduce the levels of peroxidized radicals in cells, and has anti-inflammatory and antioxidant functions. It is suitable for tissue engineering and The wound heals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005065384380000011
    Figure HDA0005065384380000011
  • Figure HDA0005065384380000012
    Figure HDA0005065384380000012
  • Figure HDA0005065384380000013
    Figure HDA0005065384380000013
Patent Text Reader

Abstract

The invention belongs to the field of polymer biomedical hydrogel materials, and particularly relates to a preparation method and application of multifunctional granular hydrogel based on ammonia-epoxy reaction. PARTICULATE HYDROGEL FORMED BY INTERCONNECTED HYDROGEL MICROPARTICLES FORMED BY CROSSLINKING OF SODIUM LIGNITONE (SL) BY PHASE SEPARATION MEDIATED BY COMPLEX BEHAVIOR BASED ON NON-COAMONIAL ACTION AND Ammonia-EPOXY CLE CHEMICAL CHEMICAL REACTION and accumulating the formed product. The preparation method comprises the following steps: adding an epoxy compound into an amino compound solution, and heating for reaction to obtain an ammonia-epoxy reaction prepolymer solution; adding a sodium lignin sulfonate solution, oscillating and mixing to obtain a prepolymer-sodium lignin sulfonate mixed solution; and adding an epoxy compound, and heating for reaction to obtain the granular hydrogel. The structure of the hydrogel is changed while sodium lignin sulfonate is introduced, and the multifunctional granular hydrogel is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer biomedical hydrogel materials, and particularly relates to a method for preparing a multifunctional granular hydrogel based on an ammonia-epoxy reaction and an application thereof. Background Art

[0002] There are many types of biomedical materials, among which hydrogel materials are favored by researchers due to their unique properties of swelling but not dissolving in water and their ability to simulate the physical and chemical properties of biological tissues. With the rapid development of materials science and life sciences, biomedical hydrogel materials have made significant progress, but there are still many challenges in the preparation and performance of hydrogels. Hydrogel materials with single performance can hardly meet the needs of various fields for advanced functionality. Therefore, preparing hydrogel materials with advanced functionality through simple and green preparation methods has become one of the current research hotspots.

[0003] In the process of studying hydrogel materials, people have found that micro-nano structures with specific geometric shapes can directly and effectively affect the biological behaviors of cells, including adhesion, migration, proliferation, and differentiation, thereby giving hydrogels many unique bionic functions. Therefore, it is of great significance to design and regulate micro-nano structures with specific geometric shapes for hydrogel materials used in the biomedical field. Granular hydrogel is a new hydrogel form, which is mainly composed of densely packed hydrogel microparticles. The difference between it and traditional hydrogels is that granular hydrogels have the characteristics of injectability and adjustable pores; in addition, since the components and structures of each microparticle are adjustable and have modular characteristics, it is possible to realize the construction of granular hydrogel materials with heterogeneous characteristics; its internal microstructure can well simulate the extracellular matrix and regulate cell behavior, and deliver nutrients, so it is widely used in tissue engineering and regenerative medicine, drug delivery, in vitro cell culture and other fields.

[0004] Sodium lignin sulfonate (SL), as a kind of lignin derivative, overcomes the problem of poor water solubility of lignin, has good water solubility, contains rich aromatic ring structures, aliphatic and aromatic hydroxyl groups and other active groups, and has excellent biological activities, such as antibacterial, antioxidant and anti-inflammatory capabilities, so it is widely introduced for the preparation of hydrogel materials. However, few literature reports that the introduction of SL can change the internal structure of the hydrogel and realize the preparation of granular hydrogel materials with a porous interconnected structure composed of interconnected microsphere particles. Summary of the invention

[0005] In view of the defects existing in the prior art, the purpose of the present invention is to provide a method for preparing a multifunctional granular hydrogel based on an amine-epoxy reaction and its application in tissue engineering, controlled drug release and wound healing. We achieve the purpose of regulating the internal microscopic morphology of the hydrogel by changing the concentration of the sodium lignin sulfonate solution or the volume ratio of the polyamino alcohol ether prepolymer solution and the sodium lignin sulfonate solution. On the one hand, the introduction of sodium lignin sulfonate gives the hydrogel antioxidant properties; at the same time, the micro-particle structure inside the hydrogel formed after the introduction of sodium lignin sulfonate can load and release hydrophobic drugs with biological functionality in response to reactive oxygen free radicals (ROS), which plays a positive role in tissue repair and wound healing. In addition, the amino group introduced by the amine-epoxy reaction has the property of being positively charged under physiological conditions, which plays a positive role in promoting cell adhesion.

[0006] In order to achieve the above-mentioned invention object, the present invention adopts the following technical solutions:

[0007] On the one hand, the present invention provides a multifunctional granular hydrogel, which is a product composed of interconnected hydrogel microparticles (Microgels) stacked by a prepolymer produced by an amine-epoxy reaction of an amino compound and an epoxy compound in water and sodium lignin sulfonate (SL) through phase separation mediated by a composite behavior based on non-covalent action and cross-linking by an ammonia-epoxy click chemistry reaction.

[0008] In the above technical solution, further, the amino compound is a compound with a molecular weight of <10000Da and containing two or more terminal groups as amino groups; the epoxy compound is a compound with a molecular weight of <10000Da and containing two or more terminal groups as epoxy groups.

[0009] In the above technical solution, further, the amino compound is 2-methyl-1,5-diaminopentane (MD); and the epoxy compound is polyethylene glycol diglycidyl ether (PEGDE).

[0010] Another aspect of the present invention provides a method for preparing the above-mentioned granular hydrogel, the method comprising:

[0011] (1) dissolving an amino compound in water to obtain an amino compound solution;

[0012] (2) adding an epoxy compound to the amino compound solution of step (1), heating the mixture to react and obtaining an ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution;

[0013] (3) dissolving sodium lignin sulfonate in water to obtain a sodium lignin sulfonate solution; adding the sodium lignin sulfonate solution to the ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution in step (2), and shaking and mixing to obtain a prepolymer-sodium lignin sulfonate mixed solution;

[0014] (4) Adding an epoxy compound to the prepolymer-sodium lignin sulfonate mixed solution of step (3), heating the mixture to react, and obtaining a granular hydrogel.

[0015] In the above technical solution, further, the concentration of the amino compound solution in step (1) is 1-50wt%.

[0016] In the above technical solution, further, in the step (2), the temperature of the heating reaction is 25-100° C., and the reaction time is 5-100 min.

[0017] In the above technical solution, further, in the step (2), the molar ratio of the amino compound to the epoxy compound is 1:3 to 4:1.

[0018] In the above technical solution, further, the concentration of the sodium lignin sulfonate solution in step (3) is 1-20wt%.

[0019] In the above technical solution, further, in the step (3), the volume ratio of the ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution to the sodium lignin sulfonate solution is 1:20 to 20:1.

[0020] In the above technical solution, further, in the step (4), the temperature of the heating reaction is 25-100° C., the reaction time is 0.1-10 h, and the mass ratio of the prepolymer-sodium lignin sulfonate mixed solution to the epoxy compound is 1:20 to 20:1.

[0021] The third aspect of the present invention provides the use of the granular hydrogel in tissue engineering, drug controlled release and wound healing.

[0022] Beneficial effects of the present invention: the present invention prepares a new granular hydrogel, which has a simple preparation process and a short preparation time. Water is used as a solvent, which is green and environmentally friendly and avoids the risk of introducing an organic solvent in the preparation of the hydrogel; at the same time, a suitable concentration of sodium lignin sulfonate is added in a specific preparation step, so that the structure of the hydrogel is changed while the sodium lignin sulfonate is introduced, and a multifunctional granular hydrogel is prepared. The amino groups in the granular hydrogel of the present invention are protonated and positively charged under physiological conditions, which is conducive to attracting cell adhesion, and its internal microscopic morphology, mechanical strength and hydrophobic drug loading capacity are adjustable; the sodium lignin sulfonate introduced in the granular hydrogel can protect cells under oxidative stress and reduce the level of intracellular peroxyl free radicals (ROS), has biological activity and the ability to load hydrophobic drugs and the ability to release drugs from ROS, and can be used as a scaffold material in the field of tissue engineering rich in ROS microenvironment, and can also be used as a controlled release system to load curcumin (Cur), a hydrophobic drug with anti-inflammatory and antioxidant functions, to reduce the inflammatory response caused by oxidative stress, and finally can also be used as a wound dressing material to promote wound healing. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Photos of the granular hydrogel samples after gelation in Examples 1-4;

[0024] Figure 2 SEM images of cross sections of freeze-dried granular hydrogel samples in Examples 1-4;

[0025] Figure 3 Infrared spectra of the granular hydrogel samples in Examples 1-4;

[0026] Figure 4 Fluorescence image of the granular hydrogel in Example 1-4 after being labeled with FITC (fluorescein isothiocyanate);

[0027] Figure 5 Fluorescence image of the granular hydrogel loaded with nile red in Example 1-4;

[0028] Figure 6 NIH3T3 cells were treated with the granular hydrogel in Example 2-4 and contained 500 μM H 2 O 2 The survival of NIH3T3 cells after 24 hours of co-culture with culture medium (***p<0.001, n=3, the mean±SD); A: Schematic diagram of the co-culture model of NIH3T3 cells and hydrogels, B: Cell survival rate after 24 hours of co-culture;

[0029] Figure 7NIH3T3 cells were treated with the granular hydrogel in Example 2-4 and contained 500 μM H 2 O 2 Fluorescence image of Calcein-AM / PI staining after co-culture with culture medium for 24 hours;

[0030] Figure 8 The loading amount of curcumin in the granular hydrogel in Examples 2-4 (n=3, the mean±SD);

[0031] Fig. 9 Evaluation of the immunocompatibility of MDPS8 particulate hydrogels themselves and curcumin-loaded MDPS8-Cur on RAW267.4 macrophages in Example 4: Fluorescent images of skeleton and nuclear staining of untreated control group and cells receiving various treatments;

[0032] Fig.10 Evaluation of the immunocompatibility of MDPS8 granular hydrogel itself and curcumin-loaded MDPS8-Cur on RAW267.4 macrophages in Example 4: spreading area of ​​cells in the untreated control group and those receiving various treatments (***p<0.001, n=3, the mean±SD);

[0033] Fig.11 Evaluation of the anti-inflammatory effects of MDPS8 particulate hydrogels themselves and curcumin-loaded MDPS8-Cur on RAW267.4 macrophages in Example 4: Representative flow cytometry plots of untreated control group and M1 [F4 / 80+, CD86+] receiving various treatments;

[0034] Fig.12 Evaluation of the anti-inflammatory effects of MDPS8 granular hydrogel itself and curcumin-loaded MDPS8-Cur on RAW267.4 macrophages in Example 4: Statistical analysis of the proportion of M1 [F4 / 80+, CD86+] macrophages in the untreated control group and those receiving various treatments (n=3);

[0035] Fig.13 Evaluation of the anti-inflammatory effects of MDPS8 granular hydrogel itself and curcumin-loaded MDPS8-Cur on RAW267.4 macrophages in Example 4: relative expression levels of (A) TNF-α, (B) IL-6 and (C) NO in the untreated control group and those receiving various treatments (compared with the LPS group, *p<0.05, **p<0.01, ***p<0.001);

[0036] Fig.14Evaluation of the effect of MDPS8 granular hydrogel itself and MDPS8-Cur loaded with curcumin on promoting healing of diabetic wounds in Example 4; A: schematic diagram of the timeline for detecting the therapeutic effect of hydrogel dressings, B: representative photos of wounds receiving various treatments, C: statistical analysis of wound area (n=4);

[0037] Fig.15 Evaluation of the effects of MDPS8 granular hydrogel itself and curcumin-loaded MDPS8-Cur on promoting healing of diabetic wounds in Example 4: H&E staining images of wounds receiving various treatments at different time points;

[0038] Fig.16 Evaluation of the effects of MDPS8 granular hydrogel itself and curcumin-loaded MDPS8-Cur on promoting healing of diabetic wounds in Example 4: Masson staining images of wounds receiving various treatments at different time points. DETAILED DESCRIPTION

[0039] The technical scheme of the present invention is further described below in conjunction with specific embodiments. These embodiments are only used for this description and are not intended to limit the scope of the invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope of protection defined by the present invention. The experimental methods for which specific conditions are not indicated in the embodiments are generally carried out according to conventional conditions and the conditions described in the experimental manual, or according to the conditions recommended by the manufacturer; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels.

[0040] Example 1

[0041] 0.435 g of the amino compound 2-methyl-1,5-diaminopentane (MD, molecular weight 116.205 Da) was added to 11.205 g of ultrapure water, shaken to dissolve, and an amino compound solution was obtained; 1.245 g of polyethylene glycol diglycidyl ether (PEGDE) was weighed, added to the previously obtained amino compound solution, shaken to mix, reacted at 65° C. in a water bath for 30 min, then cooled in an ice water bath, shaken to obtain an ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution (prepolymer-MDP); 2 mL of ultrapure water was added to 4 mL of the previously obtained prepolymer-MDP, shaken to mix, and then 800 mg of polyethylene glycol diglycidyl ether (PEGDE) was added to mix, added to a mold, sealed, and reacted at 65° C. in a water bath for 1 h to obtain a homogeneous structure MDP hydrogel with a non-porous internal microstructure.

[0042] Example 2

[0043] 0.435 g of amino compound 2-methyl-1,5-diaminopentane (MD, molecular weight 116.205 Da) was added to 11.205 g of ultrapure water, shaken to dissolve, and obtain an amino compound solution; 1.245 g of polyethylene glycol diglycidyl ether (PEGDE) was weighed, added to the previously obtained amino compound solution, shaken to mix, reacted in a water bath at 65° C. for 30 min, then cooled in an ice water bath, shaken to obtain an ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution (prepolymer-MDP); 0.15 g of sodium lignin sulfonate (SL) was added to 7.5 g of ultrapure water, shaken to dissolve, and obtain a sodium lignin sulfonate solution (wt% = 2%); 2 mL of sodium lignin sulfonate solution (wt% = 2%) was added to 4 mL of the previously obtained prepolymer-MDP, shaken to mix, and obtain a prepolymer-sodium lignin sulfonate mixed solution (MDPS2), and 6 mL MDPS2 and 800 mg of polyethylene glycol diglycidyl ether (PEGDE) were mixed, added into a mold, sealed, and reacted in a water bath at 65° C. for 1 h to obtain a granular MDPS2 hydrogel with a mesh structure having a pore size of several microns.

[0044] Example 3

[0045] 0.435 g of amino compound 2-methyl-1,5-diaminopentane (MD, molecular weight 116.205 Da) was added to 11.205 g of ultrapure water, shaken to dissolve, and obtain an amino compound solution; 1.245 g of polyethylene glycol diglycidyl ether (PEGDE) was weighed, added to the previously obtained amino compound solution, shaken to mix, reacted in a water bath at 65° C. for 30 min, then cooled in an ice water bath, shaken to obtain an ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution (prepolymer-MDP); 0.3 g of sodium lignin sulfonate (SL) was added to 7.5 g of ultrapure water, shaken to dissolve, and obtain a sodium lignin sulfonate solution (wt% = 4%); 2 mL of sodium lignin sulfonate solution (wt% = 4%) was added to 4 mL of the previously obtained prepolymer-MDP, shaken to mix, and obtain a prepolymer-sodium lignin sulfonate mixed solution (MDPS4), and 6 mL MDPS4 and 800 mg of polyethylene glycol diglycidyl ether (PEGDE) were mixed, added into a mold, sealed, and reacted in a water bath at 65° C. for 1 h to obtain an MDPS4 granular hydrogel having a porous structure composed of interconnected microsphere particles.

[0046] Example 4

[0047] 0.435 g of amino compound 2-methyl-1,5-diaminopentane (MD, molecular weight 116.205 Da) was added to 11.205 g of ultrapure water, shaken to dissolve, and obtain an amino compound solution; 1.245 g of polyethylene glycol diglycidyl ether (PEGDE) was weighed, added to the previously obtained amino compound solution, shaken to mix, reacted in a water bath at 65° C. for 30 min, then cooled in an ice water bath, shaken to obtain an ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution (prepolymer-MDP); 0.6 g of sodium lignin sulfonate (SL) was added to 7.5 g of ultrapure water, shaken to dissolve, and obtain a sodium lignin sulfonate solution (wt% = 8%); 2 mL of sodium lignin sulfonate solution (wt% = 8%) was added to 4 mL of the previously obtained prepolymer-MDP, shaken to mix, and obtain a prepolymer-sodium lignin sulfonate mixed solution (MDPS8), and 6 mL MDPS8 and 800 mg of polyethylene glycol diglycidyl ether (PEGDE) were mixed, added into a mold, sealed, and reacted in a water bath at 65° C. for 1 h to obtain an MDPS8 granular hydrogel having a porous structure composed of interconnected microsphere particles.

[0048] Experimental Example 1

[0049] Photos of the hydrogel samples of Examples 1-4 after gelation:

[0050] Figure 1 These are photos of the samples of Examples 1-4 after gelation. It can be clearly seen that with the increase in the amount of sodium lignin sulfonate (SL) introduced, the color of the hydrogels of Examples 1-4 gradually turns into dark brown, and the transparency gradually decreases. The above results preliminarily indicate that the microstructural heterogeneity in the hydrogel increases.

[0051] Experimental Example 2

[0052] Example 1-4 hydrogel morphology and structure:

[0053] Figure 2 The SEM images of Examples 1-4 show that, with the increase in the amount of sodium lignin sulfonate (SL), the internal microstructure of the hydrogels of Examples 1-4 evolves from a nonporous homogeneous structure to a porous interconnected structure composed of interconnected microsphere particles. When the concentration of SL is 0%, the internal structure of the MDP hydrogel formed is a nonporous homogeneous structure; when the concentration of SL rises to 2%, the internal structure of the MDPS2 hydrogel formed becomes a mesh structure with a pore size of several microns; until the concentration of SL rises to more than 4%, the internal structure of the MDPS4 and MDPS8 hydrogels formed are both porous structures composed of interconnected microsphere particles, and there is no statistical difference in the size of the microsphere particles between the two.

[0054] The above results show that the solubility of the added sodium lignin sulfonate solution has an important influence on the internal micromorphology of the hydrogel.

[0055] Experimental Example 3

[0056] Example 1-4 Detection of amino groups on the hydrogel surface:

[0057] We analyzed the chemical structure of the freeze-dried granular hydrogels prepared in Examples 1-4 by infrared spectroscopy, and it can be clearly seen that there are amino groups in the granular hydrogels ( Figure 3 At the same time, we used the property of fluorescein isothiocyanate (FITC) that can react with amino groups and emit fluorescence, and through confocal microscopy, we not only demonstrated the presence of amino functional groups in the hydrogels in Examples 1-4, but also further revealed that their morphology under swelling conditions was similar to that under dry conditions ( Figure 4 ).

[0058] Experimental Example 4

[0059] Example 1-4 Hydrogel loading capacity of hydrophobic drugs:

[0060] We selected the lipophilic fluorescent molecule Nile Red as a drug model and immersed the MDPS granular hydrogel (5mm×5mm×2mm) in a 0.1mg / mL Nile Red (NR) solution (acetone-water mixed solvent) at 65°C for 20min and loaded it at 4°C overnight. Rinse with ultrapure water several times to remove the unloaded Nile Red. Under a confocal microscope, it was observed that the microsphere particle structure area in the hydrogel showed a strong red fluorescence signal, indicating that NR has been successfully loaded. The microsphere particles in the granular hydrogel have the potential to load hydrophobic drugs ( Figure 5 ).

[0061] Experimental Example 5

[0062] Example 2-4 Test of the ability of hydrogel to consume peroxide free radicals (ROS) and protect cells:

[0063] In order to verify whether the granular hydrogels in Examples 2-4 have antioxidant properties and the ability to directly consume oxygen free radicals, the bioactivity of the hydrogels was evaluated by adding H 2 O 2 Under normal circumstances, a certain amount of H 2 O 2 This experiment investigated whether the antioxidant properties of the hydrogel itself can protect cells.

[0064] First, a solution containing 500 μmol / L H 2 O 2The NIH3T3 cells were co-cultured with the culture medium for 24 h, during which time 50 mg of the lyophilized granular hydrogel in Example 2-4 was added to the culture medium containing H 2 O 2 The culture medium was co-acted without H 2 O 2 The medium without hydrogel and the medium containing H 2 O 2 culture medium was used as the control group.

[0065] from Figure 6 and Figure 7 It can be seen that adding a certain amount of H 2 O 2 After the immersion in the freeze-dried granular hydrogel in Example 2-4, the cell morphology and survival of the cultured cells were improved, and as the content of sodium lignin sulfonate in the granular hydrogel increased, the cell morphology became better and better, showing a spindle shape, and the growth state was much better than that without hydrogel immersion. In particular, the cell morphology of the group of cells co-cultured after immersion in the MDPS8 hydrogel was different from that of the group of cells directly cultured without H2O. 2 O 2 The cell survival rate was also the same as that of the culture medium without H 2 O 2 The culture medium without hydrogel contained H 2 O 2 The cell survival rate of the control group of the medium was extremely low, only 28%, which was significantly different from the other groups (p<0.001). This shows that the granular hydrogel in Example 2-4 has a certain ability to directly consume oxygen free radicals and can protect cells to a certain extent.

[0066] Experimental Example 6

[0067] Example 2-4 Test of the ability of hydrogel to load curcumin:

[0068] Example 2-4 The hydrogel has the ability to load hydrophobic drugs due to its internal microsphere particle structure. Here, the hydrophobic antioxidant and anti-inflammatory drug Cur is selected and an attempt is made to load it using the microsphere particle structure in the hydrogel. Figure 8 It can be seen that the results are consistent with those of the Nile red loading experiment ( Figure 5 ), MDPS8 hydrogel showed the strongest Cur loading capacity, exceeding 2.28 mg curcumin / g hydrogel, while the MDPS2 sample with relatively inconspicuous spherical particle morphology had the smallest loading capacity, only 1.12 mg curcumin / g hydrogel.

[0069] Experimental Example 7

[0070] Example 4 Evaluation of immunocompatibility of hydrogel before and after loading with curcumin:

[0071] To evaluate whether the granular hydrogel can induce cellular immune response, we took the MDPS8 hydrogel in Example 4 as an example and selected RAW267.4 macrophages to evaluate the inflammatory stimulation of the MDPS8 hydrogel itself and the MDPS8 hydrogel loaded with curcumin (MDPS8-Cur). Fig. 9 and Fig.10 It can be seen that, unlike the enlarged cell body morphology of RAW267.4 macrophages activated by LPS, the macrophages in the MDPS8 group and MDPS8-Cur experimental group all showed normal round morphology, which was similar to the cell morphology of the blank control group without LPS activation. This shows that the MDPS8 hydrogel itself and the MDPS8-Cur loaded with curcumin in Example 4 have good immune compatibility and will not cause immune activation of macrophages.

[0072] Experimental Example 8

[0073] Example 4 Evaluation of the anti-inflammatory ability of hydrogel loaded with curcumin:

[0074] To evaluate whether the granular hydrogel loaded with curcumin has anti-inflammatory function, we selected the MDPS8 hydrogel in Example 4 as an example to load curcumin, and evaluated the anti-inflammatory ability of MDPS8-Cur by LPS-activated RAW267.4 macrophages. Fig.11 and Fig.12 It can be seen that after LPS stimulation, the proportion of M1 macrophages increased significantly (p<0.01). After the action of MDPS8-Cur, the proportion of M1 macrophages decreased. In addition, we also quantitatively evaluated the inhibitory effect of MDPS8-Cur on the inflammatory factors NO, TNF-α and IL-6 secreted by LPS-activated RAW267.4 macrophages. After LPS stimulation, the content of each inflammatory factor was significantly increased compared with the negative control group (p<0.001). After the action of MDPS8-Cur, the activated RAW267.4 macrophages showed a decrease in the release levels of NO, TNF-α and IL-6, indicating that the cells absorbed the curcumin released into the culture medium and reduced the activation effect of LPS ( Fig.13 The above results indicate that this type of MDPS granular hydrogel material can achieve anti-inflammatory functionality by loading curcumin, has the potential to be used as a hydrophobic drug delivery system, and can be applied in specific biomedical fields, such as the treatment of inflammatory disorders.

[0075] Experimental Example 9

[0076] In order to verify whether MDPS granular hydrogel has the potential to be applied in wound healing, we took the MDPS8 hydrogel in Example 4 as an example and evaluated the healing effect of MDPS8 hydrogel itself and MDPS8 hydrogel loaded with curcumin (MDPS8-Cur) on diabetic chronic wounds using an animal model of diabetic skin wounds. Fig.14 It can be seen that compared with the blank control group and the commercial gelatin sponge control group without any intervention, MDPS8 hydrogel and MDPS8-Cur loaded with curcumin showed stronger ability to promote wound healing. In addition, we performed H&E staining and Masson staining on the wound tissues treated with different dressing materials ( Fig.15 and 16 ), and its histological analysis results were consistent with the wound healing rate; and on the 14th day, dense granulation tissue and new collagen were observed in both MDPS8 and MDPS8-Cur, but not in the control group, indicating the potential of MDPS granular hydrogel in promoting diabetic wound healing.

[0077] For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A granular hydrogel, characterized in that The granular hydrogel is a product composed of interconnected hydrogel microparticles (Microgels) stacked by a prepolymer produced by an amine-epoxy reaction of an amino compound and an epoxy compound in water and sodium lignin sulfonate (SL) through phase separation mediated by a composite behavior based on non-covalent interaction and cross-linking by an ammonia-epoxy click chemical reaction.

2. The granular hydrogel according to claim 1, characterized in that The amino compound is a compound with a molecular weight of less than 10000Da and containing two or more terminal amino groups; the epoxy compound is a compound with a molecular weight of <10000Da compounds containing two or more terminal epoxy groups.

3. The granular hydrogel according to claim 2, characterized in that The amino compound is 2-methyl-1,5-diaminopentane (MD); and the epoxy compound is polyethylene glycol diglycidyl ether (PEGDE).

4. A method for preparing the granular hydrogel according to claim 1, characterized in that: The method is: (1) dissolving an amino compound in water to obtain an amino compound solution; (2) adding an epoxy compound to the amino compound solution of step (1), heating the mixture to react and obtaining an ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution; (3) dissolving sodium lignin sulfonate in water to obtain a sodium lignin sulfonate solution; adding the sodium lignin sulfonate solution to the ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution in step (2), and shaking and mixing to obtain a prepolymer-sodium lignin sulfonate mixed solution; (4) Adding an epoxy compound to the prepolymer-sodium lignin sulfonate mixed solution of step (3), heating the mixture to react, and obtaining a granular hydrogel.

5. The method for preparing the granular hydrogel according to claim 4, characterized in that: The concentration of the amino compound solution in step (1) is 1-50 wt %.

6. The method for preparing the granular hydrogel according to claim 4, characterized in that: The heating reaction temperature in step (2) is 25-100° C. and the reaction time is 5-100 min.

7. The method for preparing the granular hydrogel according to claim 4, characterized in that: The molar ratio of the amino compound to the epoxy compound in step (2) is 1:3 to 4:

1.

8. The method for preparing the granular hydrogel according to claim 4, characterized in that: The concentration of the sodium lignin sulfonate solution in step (3) is 1-20wt%; the volume ratio of the ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution to the sodium lignin sulfonate solution is 1:20 to 20:

1.

9. The method for preparing the granular hydrogel according to claim 4, characterized in that: The temperature of the heating reaction in step (4) is 25-100° C., the reaction time is 0.1-10 h, and the mass ratio of the prepolymer-sodium lignin sulfonate mixed solution to the epoxy compound is 1:20 to 20:

1.

10. Use of the granular hydrogel according to claim 1 in tissue engineering, drug controlled release and wound healing.